El aseguramiento de la calidad en carreras de grado no acreditables: Reflexiones sobre el caso Argentino; Quality assurance in non-accreditable undergraduate programs: Reflections on the Argentine case - Sebastián Rinaldi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
– In this paper, proposals for quality assurance in non-accreditable undergraduate programs are made, in accordance with the current regulatory framework in the Argentine higher education system. For this purpose, an approximation to the concept of quality is stated and the criteria that programs must accomplish to be evaluated by the national agency for university evaluation and accreditation are analysed. To conclude, the existence of various mechanisms that can stimulate the improvement of the quality of academic trainings, based on a greater integration of institutions and a strengthening of professional groups, is determined
Keywords: 330; Aseguramiento de la calidad; acreditación; evaluación; universidad; carrerasde grado; Quality assurance; accreditation; assessment; university; undergraduate programs